Biochemical, Physiological, and Molecular Aspects of Ornamental Plants Adaptation to Deficit Irrigation - Maria Giordano; Spyridon A. Petropoulos; Chiara Cirillo; Youssef Rouphael (Horticulturae, 2021)
There is increasing concern regarding global warming and its severe impact on the farming sector and food security. Incidences of extreme weather conditions are becoming more and more frequent, posing plants to stressful conditions, such as flooding, drought, heat, or frost etc. Especially for arid lands, there is a tug-of-war between keeping high crop yields and increasing water use efficiency of limited water resources. This difficult task can be achieved through the selection of tolerant water stress species or by increasing the tolerance of sensitive species. In this scenario, it is important to understand the response of plants to water stress. So far, the response of staple foods and vegetable crops to deficit irrigation is well studied. However, there is lack of literature regarding the responses of ornamental plants to water stress conditions. Considering the importance of this ever-growing sector for the agricultural sector, this review aims to reveal the defense mechanisms and the involved morpho-physiological, biochemical, and molecular changes in ornamental plant’s responses to deficit irrigation.